Analisis Pusat Pertumbuhan Wilayah dan Hinterland di Kabupaten Kulon Progo: Indonesia - Hanifah, Jihan; Priyadi, Unggul (Asian Journal of Innovation and Entrepreneurship, 2025)
This study aims to determine the sub-districts that have the potential to be growth centers and hinterland areas in Kulon Progo Regency and to analyze the magnitude of the interaction between growth centers and supporting areas. This type of research is quantitative descriptive using scalogram analysis and gravity analysis methods. This study was processed using Microsoft Excel 2013. The results of the scalogram analysis study show that in 2020 there were three sub-districts as growth centers in Kulon Progo Regency, namely Wates District, Temon District, and Nanggulan District. In 2023, the three sub-districts will remain growth centers. The results of the gravity analysis revealed differences in distance between sub-districts which affect the magnitude of interaction between the growth center sub-districts and the Hinterland.